M-libraries 4: from margin to mainstream – mobile technologies transforming lives and libraries. Issue 4 (19th August 2014) - Yeates, Robin; Sicilia, Miguel-Angel; Eyre, John
<x content-type="archive" xml:space="preserve">Abstract</x>